Bowel Lymphoma in Children: Management and Outcome - Veerabhadra, R; Kumar, G Krishna; Bibekanand, J; Kumar, N Bikash; Kumaravel, S; Bhawana, B; Biswajit, D (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Primary bowel lymphoma is an uncommon neoplasm in children and not well documented in literature with regard to its outcome and management. Materials and Methods: A case record review of children with bowel lymphoma was undertaken in a tertiary care institute, from 2010 to 2016 and the relevant data were recorded. Results: 21 children were managed with bowel lymphoma over a period of 7 years. Pain abdomen was the most common presenting symptom (19/21). Ileum was the site of involvement in most children (17/21). Localised disease was seen in 13/21 while 8 had diffuse involvement. Predominantly (13/21) children presented at an advanced stage (III/IV). Surgical intervention was needed in 14/21 while 7/21 were managed only with chemotherapy. Majority (15/21) had Burkitt's lymphoma on histology. 13 of 21 (61.9%) have completed chemotherapy and on regular follow up. Among 8 who died, 6 were directly related to disease progression despite aggressive management. Conclusion: Bowel lymphoma in children is distinctly different in the site of presentation from that of the adults. Advanced stage at presentation portends poor prognosis. Bowel lymphoma is to be considered in case of recurrent intussusception in children.
Keywords: Bowel lymphoma; Burkitt's lymphoma; childhood malignancies; non-Hodgkin's lymphoma